The Effect of Billboard Ads and Social Media on Brand Awareness - Wasserbauer, Michal (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2023)
This study discusses the influence of billboard advertising and social media on brand awareness is a literature review scientific article. The purpose of writing this article is to build a hypothesis of influence between variables that can be used in further research, within the scope of marketing management science. The method of writing articles is quantitative, data obtained from questionnaires submitted to respondents via google form with several indicators related to billboard advertisements and social media. The population in this study amounted to 200 people with a research sample of 50 respondents. The sampling technique used is accidental sampling. The tests carried out are t-tests, f-tests and determination coefficient tests. The results of this study include: 1) Billboard advertising has an effect on brand awareness partially; 2) Social media has a partial effect on brand awareness; and 3) Billboard advertising and social media affect brand awareness simultaneously. Apart from these 2 exogen variables that affect endogenous variables of brand awareness, there are still other factors including promotion, co-branding and advertising.